A study on how married women managers in the non-government organizations in Iloilo City manage their work and family responsibilities - Bantolo, Jocelyn B. (1995.)
Women of today are no longer content to stay at home and be busy rearing the children or taking care of the home. In short they have joined the work force not only for their own personal and professional growth, but also to be able to provide their families with the financial support they need. Because of these reasons they are faced with much complicated situation wherein the have to balance work and family commitments. It is in this connection that our study was formed. A study entitled "How do women managers manage their work and family responsibilities?". This is an attempt to find out the different strategies and actions of the women managers to come up with a more balanced family responsibilities and work obligations through the following: 1) by identifying the work activities of a woman manager at home and in the office; 2) by learning the time allocated by a woman manager to her family, home responsibilities and work in the office; 3) by determining the management skills being applied at the office and at home; 4) by determining the effects of holding multiple responsibilities; and 5) by being able to assess how a woman manager manages her work and family responsibilities. Frequency distribution was used in answering the above mentioned objectives.
Research Paper (BA 200 - Business Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 1995.